An overview of the structure and future prospects of China’s Urban and Rural Resident Pension Insurance (URRPI) / Wang Hanjue, Thenmolli Vadeveloo and Suhaimi Abd. Samad - Hanjue, Wang; Vadeveloo, Thenmolli; Abd. Samad, Suhaimi (Faculty of Administrative Science and Policy Studies, 2025)
Urban and Rural Resident Pension Insurance (URRPI) is a significant component of the social security framework, aimed at promoting equal access to old-age security public services. This study systematically organizes the institutional structure of the URRPI using qualitative research methods. The URRPI’s system structure consists of five main components: the responsible body, beneficiary composition, financing mode, payment mode, and operational mode. The analysis has revealed shortcomings in the current financing, payment, and operational models of the URRPI system. Several suggestions have been proposed to address the challenges faced during its implementation regarding the institutional composition of URRPI. These include enhancing financing capabilities, improving the payment process, and optimizing the operational capacity of pension insurance funds. Through these measures, it is expected that URRPI will better meet the needs of China’s social development, alleviate the pressure of population aging, and provide more equitable and sustainable pension security for insured residents.